A Novel HVDC Architecture for Offshore Wind Farm Applications - Dezem Bertozzi Junior, Otávio José (2020)
The increasing global participation of wind power in the overall generation ca- pacity makes it one of the most promising renewable resources. Advances in power electronics have enabled this market growth and penetration. Through a literature review, this work explores the challenges and opportunities presented by offshore wind farms, as well as the different solutions proposed concerning power electron- ics converters, collection and transmission schemes, as well as control and protection techniques. A novel power converter solution for the parallel connection of high power offshore wind turbines, suitable for HVDC collection and transmission, is presented. For the parallel operation of energy sources in an HVDC grid, DC link voltage con- trol is required. The proposed system is based on a full-power rated uncontrolled diode bridge rectifier in series with a partially-rated fully-controlled thyristor bridge rectifier. The thyristor bridge acts as a voltage regulator to ensure the flow of the desired current through each branch, where a reactor is placed in series for filtering of the DC current. AC filters are installed on the machine side to mitigate harmonic content. The mathematical modeling of the system is derived and the control design procedure is discussed. Guidelines for equipment and device specifications are pre- sented. Different setups for an experimental framework are suggested and discussed, including a conceptual application for hardware-in-the-loop real-time simulation and testing.